Reliability and validity of the online Pittsburgh sleep quality index in college students from low-income regions - De Moraes, Augusto César Ferreira; Conceição da Silva, Lorrane Cristine; Lima, Barbara Saldanha; Marin, Kliver Antonio; Hunt, Ethan T.; Nascimento-Ferreira, Marcus Vinicius (Frontiers in Digital Health, 2024)
ObjectivesWe aimed to test the reliability and structural validity (also called dimensionality) of the online Pittsburgh Sleep Quality Index among college students from low-income regions.MethodsWe assessed 195 Brazilian college students from a low-income region (Gini index of 0.56), of whom 117 were reassessed to evaluate the reliability. We collected all data in a self-reported online twice, 2-week apart. We evaluated reliability and structural validity.ResultsAll questionnaire components showed reliability, correlation coefficient ≥0.49. In the structural validity, the confirmatory analysis showed better global model adjustment for the one-factor (RMSEA = 0.019; SRMR = 0.041; CFI = 0.992; TLI = 0.986) solution compared with two-factor (RMSEA = 0.099; SRMR = 0.070; CFI = 0.764; TLI = 0.619) and three-factor (RMSEA = 0.108; SRMR = 0.066; CFI = 0.763; TLI = 0.548) solutions, respectively.DiscussionThe online questionnaire presents acceptable reliability and structural validity in Brazilian low-income regions.